Centriolar satellites: busy orbits around the centrosome - Bärenz, Felix; Mayilo, Dmytro; Gruss, Oliver (European journal of cell biology, 2011)
Since its first description by Theodor Boveri in 1888, the centrosome has been studied intensely, and it revealed detailed information about its structure, molecular composition and its various functions. The centrosome consists of two centrioles, which generally appear in electron microscopy as barrel-shaped structures usually composed of nine microtubule triplets. An amorphous mass of pericentriolar material surrounds the centrioles and accumulates many proteins important for the integrity and function of centrosomes, such as the γ-tubulin ring complex (γ-TuRC) that mediates microtubule nucleation and capping. In animal somatic cells, the centrosome generally accounts for the major microtubule organizing center, and the duplicated pair of centrosomes determines the poles of the microtubule-based mitotic spindle. Despite detailed insights into the centrosome's structure and function, it has been a complete mystery until a few years ago how centrosomes duplicate and assemble. Moreover, it is still largely unclear if and how centrosomal proteins or protein complexes are exchanged, replaced or qualitatively altered. Previously identified cytoplasmic granules, named “pericentriolar” or “centriolar satellites”, might fulfil such functions in protein targeting and exchange, and communication between the centrosomes and the cytoplasm. In this review, we summarize current knowledge about the structure, molecular composition and possible roles of the satellites that seem to surround the core of the centrosome in most animal cells.